Optimizing Green Waqf as a Solution to Overcome Environmental Crisis - Anwar, Khairul; Sarasi, Vita; Ubaidillah, Ubaidillah; Masnu'ah, Siti; Wahidah, Nurul (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2025)
The environmental crisis has been a problem for a long time, in fact environmental degradation is getting worse from year to year. One solution to minimize environmental damage is green waqf. The aim of this research is to describe and analyze the implementation of green waqf in Indonesia, as well as analyze the reasons why green waqf can be a solution to environmental damage. This research falls into the category of library research or "library research". The approach taken is qualitative. Data sources are secondary sources, namely collecting, understanding and analyzing previous articles, news and books on relevant topics. The research results show that in Indonesia, the green waqf movement has not been implemented very much. There are at least four activities that can be called green waqf, namely tamanu tree waqf, clean water source waqf, forest waqf, and mangrove tree waqf. Tamanu trees are beneficial for unproductive land, clean water can benefit the community and provide long-term access to life, waqf forests play a role in maintaining microclimate stability, preserving biodiversity, conserving air, and preventing natural disasters, while mangrove trees provide benefits for the environment coastline. The implication of this research is to create public awareness to maximize the potential of waqf, especially environmentally friendly waqf.